Eficiência energética de seleção de relays em um sistema cooperativo MIMO com codificação de rede - Chiodi Junior, Marco Antonio (2021)
In this work, we evaluate the energy efficiency of a recently proposed network-coded cooperative scheme with multiple relay selection, in a scenario with multiple sources and a single common destination. By considering that all the nodes and also the destination are equipped with multiple antennas, we compare the EE of the network when operating under two different combination techniques at the receiver side, namely selection combining (SC) and maximum ratio combining (MRC) techniques. Our analysis, which also encompasses the circuitry consumption of all the nodes in the network, shows that the MRC scheme, which is optimal from a reliability perspective, may be outperformed by the SC scheme when the EE is adopted as the performance metric. Based on insights about the number of relays that must be used to optimize EE, an improvement in the system is proposed in order to raise network energetic efficiency, the incremental multiple relay selection (INC-MRS). Finally, numerical results are presented in order to support all the mathematical analyses.